The Implementation of Jigsaw Strategy to Improve Students’ Active Participation in Learning of Tarjamah, Class of Grade 4 KMI at Third Campus of Darussalam Gontor Islamic Boarding School Academic Year: 1438-1439 H - Muhyiddin, Luthfi; Zharfa, Hazrati (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2018)
The Implementation of Jigsaw Strategy to Improve Studentsâ€™ Active Participation in Learning of Tarjamah, Class of Grade 4 KMI at Third Campus of Darussalam Gontor Islamic Boarding School Academic Year: 1438-1439 H Â Luthfi Muhyiddin, Hazrati Zharfa luthfimuhyiddin@unida.gontor.ac.id, hazratizharfa@gmail.com University of Darussalam Gontor Â ABSTRACT Darussalam Gontor Islamic Boarding School is one of the biggest pesantren in East Java which teaches both religion and academic subjects for the same 100%. One of subjects taught is Tarjamah which serves as a very important subject. As an attempt to make it easier for teachers to teach the subject as well as for students not to be bored in the teaching and learning activity, it is essential for the teachers to choose and implement a suitable teaching strategy. One of the suitable strategies in Tarjamah subject is Jigsaw. This study aims at (1) describing teaching steps in Tarjamah subject using Jigsaw strategy (2) knowing the improvement of studentsâ€™ active participation using Jigsaw teaching strategy. This study is a Classroom Action Research (CAR), that is, a study which is implemented by a teacher in his own classroom using qualitative research design. This study consists of 2 cycles and each cycle consists of 4 steps which are: designing, implementing, observing, and reflecting. Data collection techniques which are used are: (1)observation on studentsâ€™ active participation, (2)interview, (3)documentation, in which the data is analyzed using Miles and Huberman theory covering 3 steps which are: Data reduction, Data presentation, and Conclusion. From the data analysis, it is shown that (1) there are 7 steps in implementing Jigsaw strategy in Tarjamah subject which are: the teacher entered the classroom by saying salam, the teacher explained the materials which will be learnt, the students were divided into one group, students sat on their group, the students were given materials by the teacher, each group discussed the materials, after the students were finished discussing, they formed new groups to present the materials they had learnt, the teacher gave evaluation on studentsâ€™ presentation. (2) the implementation of Jigsaw strategy in Tarjamah subject can improve studentsâ€™ active participation in learning which can be seen from the conducive learning atmosphere during the teaching and learning activity as well as the studentsâ€™ opinion who expressed their happiness and enthusiasm on the implementation of this strategy. Keywords: Jigsaw strategy, teaching and learning activity, translation, santriwati, teacher, semester, teaching curriculum. Â ØªÙ†ÙÙŠØ° Ø¥Ø³ØªØ±Ø§ØªØ¨Ø¬Ø¨Ø© Ø¬ÙƒØ³Ùˆ (Jigsaw) Ù„ØªØ±Ù‚ÙŠØ© Ù†Ø´Ø§Ø· Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª ÙÙŠ ØªØ¹Ù„Ù… Ù…Ø§Ø¯Ø© Ø§Ù„ØªØ±Ø¬Ù…Ø© Ù„Ù„ÙØµÙ„ Ø§Ù„Ø±Ø§Ø¨Ø¹ F Ø¨ÙƒÙ„ÙŠØ© Ø§Ù„Ù…Ø¹Ù„Ù…Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø±Ø§Ù„Ø³Ù„Ø§Ù… ÙƒÙˆÙ†ØªÙˆØ± Ù„Ù„Ø¨Ù†Ø§Øª Ø§Ù„ØØ±Ù… Ø§Ù„Ø«Ø§Ù„Ø« Ø§Ù„Ø¹Ø§Ù… Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠ 1438-1439 Ù‡ Ù„Ø·ÙÙ‰ Ù…ØÙŠÙ‰ Ø§Ù„Ø¯ÙŠÙ†ØŒ ØØ¶Ø±ØªÙŠ Ø¶Ø±ÙÙ‰ luthfimuhyiddin@unida.gontor.ac.id, hazratizharfa@gmail.com Ø¬Ø§Ù…Ø¹Ø© Ø¯Ø§Ø± Ø§Ù„Ø³Ù„Ø§Ù… Ù…Ù„Ø®Øµ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ø³Ù„Ø§Ù… ÙƒÙˆÙ†ØªÙˆØ± Ù…Ù† Ø£ÙƒØ¨Ø± Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ ÙÙŠ Ø¬Ø§ÙˆÙ‰ Ø§Ù„Ø´Ø±Ù‚ÙŠØ© Ø§Ù„Ø°ÙŠ ØªØ¹Ù„Ù… Ù…Ø§Ø¦Ø© Ù…Ù† Ù…Ø§Ø¦Ø© Ø§Ù„Ø¹Ù„ÙˆÙ… Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© ÙˆÙ…Ø§Ø¦Ø© Ù…Ù† Ù…Ø§Ø¦Ø© Ø§Ù„Ø¹Ù„ÙˆÙ… Ø§Ù„ÙƒÙˆÙ†ÙŠØ©. ÙˆÙ…Ù† Ø¥ØØ¯Ù‰ Ø§Ù„Ø¯Ø±ÙˆØ³ Ø§Ù„ØªÙŠ ØªØ¹Ù„Ù‘Ù… ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø±Ø§Ù„Ø³Ù„Ø§Ù… Ù„Ù„ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø®Ø¯ÙŠØ«Ø© ÙƒÙˆÙ†ØªÙˆØ± Ù‡ÙŠ Ø§Ù„ØªØ±Ø¬Ù…Ø©ØŒ Ø£Ù‡Ù… Ø§Ù„Ø¯Ø±Ø³ Ù„Ù„ØºØ©.ÙˆÙ„ØªÙƒÙˆÙ† Ø§Ù„Ù…Ø¹Ù„Ù…Ø© Ù†Ø§ØØ© ÙÙŠ ØªØ¹Ù„ÙŠÙ…Ù‡Ø§ ÙˆÙ„Ø§ ØªØ´Ø¹Ø± Ø§Ù„Ù…ØªØ¹Ù„Ù… Ù…ØªØ³Ø§Ø¦Ù…Ø© ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„ØªØ¹Ù„Ù… ÙÙ„Ø§ Ø¨Ø¯ Ù„Ù‡Ø§ Ø§Ù„Ù…Ù‡Ø§Ø±Ø© ÙÙŠ Ø§Ø®ØªÙŠØ§Ø± ÙˆØªÙ†ÙÙŠØ° Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù…. ÙˆØ¥ØØ¯Ù‰ Ù…Ù† Ø§Ù„Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø© ÙˆÙ‡ÙŠ Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø¬ÙƒØ³Ùˆ. Ø§Ù„Ù‡Ø¯Ù Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù„Ù„ÙƒØ´Ù Ø¹Ù† (1) Ø®Ø·ÙˆØ§Øª Ø§Ù„ØªØ¯Ø±ÙŠØ³ Ø¨Ø§Ù„Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø¬ÙƒØ³Ùˆ ÙÙŠ Ù…Ø§Ø¯Ø© Ø§Ù„ØªØ±Ø¬Ù…Ø© (2) ÙØ¹Ø§Ù„ÙŠØ© ØªØ±Ù‚ÙŠØ© Ù†Ø´Ø§Ø· Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ø¨ØªÙ†ÙÙŠØ° Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù… Ø¬ÙƒØ³Ùˆ. ÙŠØ³ØªØ®Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¹Ù…Ù„ÙŠØ© Ø§Ù„Ø¨ØØ« ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠ (CAR) ÙˆÙ‡ÙŠ Ø§Ù„Ø¨ØØ« Ø§Ù„Ø°ÙŠ Ø¹Ù‚Ø¯ØªÙ‡ Ø§Ù„Ù…Ø¹Ù„Ù…Ø© ÙÙŠ ÙØµÙ„Ù‡Ø§ØŒ ÙˆÙƒØ§Ù†Øª Ø¹Ù…Ù„ÙŠØ© Ø§Ù„Ø¨ØØ« ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠ Ù…Ù† Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ÙƒÙŠÙÙŠØ©. ÙˆÙŠØªÙƒÙˆÙ† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…Ù† Ø§Ù„Ø¯ÙˆØ±ÙŠÙ† ÙˆÙÙŠ ÙƒÙ„ Ø¯ÙˆØ± ÙŠØ´Ù…Ù„ Ø¹Ù„Ù‰ Ø£Ø±Ø¨Ø¹ Ù…ÙˆØ§ØÙ„ ÙˆÙ‡ÙŠ: Ø§Ù„ØªØ®Ø·ÙŠØ·ØŒ Ø§Ù„ØªÙ†ÙÙŠØ°ØŒ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø©ØŒ ÙˆØ§Ù„Ù…Ù†Ø¹ÙƒØ³Ø©. ÙˆØ§Ù„Ù…Ù†Ø§Ù‡Ø¬ Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù„Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù‡ÙŠ: (1) Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© Ø§Ù„Ø§Ø´ØªØ±Ø§ÙƒÙŠØ© Ø¹Ù† Ù†Ø´Ø§Ø· Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª (2) Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© (3) Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØ³Ø§Ø¦Ù‚ Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø©. ÙˆØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø§Ù„Ù…Ù†Ù‡Ø¬ Ù…Ù„ÙŠØ³ ÙˆÙ‡ÙˆØ¨ÙŠØ±Ù…Ø§Ù† (Miles and Huberman) Ø§Ù„Ø°ÙŠ ÙŠØØªÙˆÙŠ Ø¹Ù„Ù‰ Ø«Ù„Ø§Ø« Ø®Ø·ÙˆØ§ØªØŒ ÙˆÙ‡ÙŠ: (1) ØªØ®ÙÙŠØ¶ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª (2) Ø¹Ø±Ø¶ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª (3) Ø§Ù„Ø§Ø³ØªÙ†ØªØ§Ø¬ Ùˆ Ø§Ù„ØªØÙ‚ÙŠÙ‚. ÙˆÙ†ØªÙŠØ¬Ø© Ø§Ù„Ø¨ØØ« Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« (1) ÙƒØ§Ù† Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø¨ØªÙ†ÙÙŠØ° Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø¬ÙƒØ³Ùˆ (Jigsaw) ØªØØªÙˆÙŠ Ø¹Ù„Ù‰ Ø³Ø¨Ø¹Ø© Ø®Ø·ÙˆØ§Øª ÙˆÙ‡ÙŠ: Ø¯Ø®Ù„Øª Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ÙØµÙ„ Ø¨Ø¥Ù„Ù‚Ø§Ø¡ Ø§Ù„Ø³Ù„Ø§Ù… Ø«Ù… Ø§Ù„Ù…Ù‚Ø¯Ù…Ø©ØŒ Ø´Ø±ØØª Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…Ø§Ø¯Ø© Ø§Ù„ØªÙŠ Ø¹ÙŠÙ†Øª Ù†Ù‚Ù„Ù‡Ø§ØŒ Ù‚Ø³Ù…Øª Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø¥Ù„Ù‰ Ø®Ù…Ø³Ø© ÙØ±ÙˆÙ‚ ÙˆÙ„ÙƒÙ„ ÙØ±Ù‚Ø© ØªØªÙƒÙˆÙ† Ø¹Ù„Ù‰ Ø«Ù…Ø§Ù†ÙŠ Ø·Ø§Ù„Ø¨Ø§ØªØŒ Ø£Ù…Ø±Øª Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ù„Ù„Ø¬Ù„ÙˆØ³ ØØ³Ø¨ Ø§Ù„ÙØ±Ù‚Ø©ØŒ Ø£Ø¹Ø·Øª Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…Ø§Ø¯Ø© Ø¥Ù„Ù‰ ÙƒÙ„ ÙØ±Ù‚Ø© Ù„ÙŠÙ†Ø§Ù‚Ø´Ù†ØŒ ÙˆÙ„ÙƒÙ„ Ù†ÙØ± ØªÙƒÙˆÙ† ÙØ±ÙŠÙ‚ Ø§Ù„Ø®Ø¨Ø±Ø§Ø¡ØŒ ÙØ¨Ø¹Ø¯ Ø§Ù„Ù…Ù†Ø§Ù‚Ø´Ø©ØŒ Ø£Ù…Ø±Øª Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ù„ÙŠØ¬ØªÙ…Ø¹Ù† Ø¨ÙØ±Ù‚Ø© Ø£Ø®Ø±Ù‰ Ù„ØªÙ„Ù‚ÙŠ Ù…Ø§ Ù†Ù‚Ø´ØªØŒ Ø£Ù„Ù‚Øª Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ØªÙ‚ÙŠÙŠÙ…Ø§Øª Ø¹Ù† Ø§Ù„Ù…Ø§Ø¯Ø© Ø§Ù„ØªÙŠ Ù†Ù‚Ø´Øª.(2) ÙƒØ§Ù† ØªÙ†ÙÙŠØ° Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø¬ÙƒØ³Ùˆ (Jigsaw) ØªØ±Ù‚ÙŠ Ù†Ø´Ø§Ø· Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ø¹Ù†Ø¯ Ø§Ù„ØªØ¹Ù„Ù…. Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠØ©: Ø£Ø³ØªØ±Ø§ØªÙŠØ¬Ø© Ø¬ÙƒØ³ÙˆØŒ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ØŒ Ø§Ù„ØªØ±Ø¬Ù…Ø©ØŒ Ø§Ù„Ø·Ø§Ù„Ø¨Ø§ØªØŒ Ø§Ù„Ù…Ø¯Ø±Ù‘Ø³Ø©ØŒ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¯Ø§Ø±Ø³ÙŠØŒ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠ.